Tax implications of Brexit - Saccardo, Nicola (London [England] : Bloomsbury Professional, 2021)
"Tax Implications of Brexit is an essential guide for anyone advising businesses trading in either the United Kingdom or the European Union post-Brexit. In two parts, this title provides an in-depth analysis of the tax ramifications of Brexit in both the United Kingdom and EU Member States, helping to identify immediate and future issues that could be faced post-Brexit, and how to mitigate any risks. Part One features subject-specific chapters which deal with the UK statutory regime after 2020 as well as the impact of Brexit on VAT, customs and excise duties and State Aid legislation. Part Two is split into country chapters dealing with the tax implications in the single jurisdictions (the United Kingdom and EU Member States) for cross-border investments between the United Kingdom and the EU and for UK-EU cross-border reorganisations. This book is essential reading for tax professionals advising businesses trading in the United Kingdom or in the European Union, but also tax managers of those businesses. Tax Implications of Brexit includes contributions from Barbara Belgrano, Conor Quigley QC, Julian Ghosh QC, Kelly Stricklin-Coutinho, Nicola Saccardo, Roderick Cordara QC, Timothy Lyons QC and a plethora of highly respected tax experts from EU jurisdictions."--
Part 1: General -- Chapter 1: EU Law in the United Kingdom Post-31 December 2020: The Statutory Regime -- Chapter 2: Brexit Implications for VAT -- Chapter 3: Customs and Excise and Brexit -- Chapter 4: Brexit Implications for State Aid Legislation Part 2: Countries -- Chapter 5: Austria -- Chapter 6: Belgium -- Chapter 7: Czech Republic -- Chapter 8: Denmark -- Chapter 9: France -- Chapter 10: Germany -- Chapter 11: Hungary -- Chapter 12: Republic of Ireland -- Chapter 13: Italy -- Chapter 14: Luxembourg -- Chapter 15: The Netherlands -- Chapter 16: Poland -- Chapter 17: Portugal -- Chapter 18: Spain -- Chapter 19: Sweden -- Chapter 20: United Kingdom
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Taxation -- Great Britain; Taxation -- Europe; Taxation; Electronic books